A Literature Review of Empirical Studies on Empowering GIDA Schools Through AI-Based Academic Data Management - Chona Libona (Southeast Asian Journal of Science and Technology, 2025)
This study presents a systematic literature review of empirical research on the use of artificialintelligence (AI)–based academic data management systems in Geographically Isolated and DisadvantagedAreas (GIDA) schools. The review synthesizes studies addressing persistent challenges faced by GIDA schools,including limited infrastructure, scarce resources, and constraints in accessing qualified personnel andlearning materials. Using established systematic review procedures, the study examines current academic datamanagement practices, feasibility considerations for AI integration in low-resource settings, and AItechnologies reported as suitable for geographically isolated school contexts. The reviewed literature indicatesthat while AI-driven academic data systems have demonstrated benefits in improving administrative efficiency,data accuracy, and decision-making in well-resourced schools, their application in GIDA schools remainslimited. Nevertheless, evidence suggests that context-appropriate AI solutions—particularly those supportingoffline functionality, low-bandwidth operation, and user-friendly interfaces—hold significant potential forstrengthening academic data management and promoting educational equity. The findings underscore theimportance of aligning AI initiatives with local conditions, capacity-building efforts, and national educationpolicies to support inclusive digital transformation in GIDA schools.